The Formation of National Identity and its’ Sociopsychological Interpretations - Antinienė, Dalia (Sociologija. Mintis ir veiksmas, 2002)
The aim of this article is to analyse important dimension of a personal identity, i.e. the nature of the national identity, its characteristic features and the socio-psychological issues of its’ formation. National identity is a complex and dynamic phenomenon. The article contrasts a number of theoretical approaches - impact of childhood and socialization upon its’ formation, possible shifts throughout the whole life; the “latent” character of national identity which is being publicly manifest only in specific historic circumstances of a person, his (her) family, country, etc. The process whereby a person’s identity is shaped through his (her) identification vis-a-vis Significant Others is addressed in the paper as well. Other dimensions of national identity formation and meanings, e.g. commitment, attachment, needs, “national sentiments”, “affective involvement”, etc. are analysed and contrasted. For the research of national identity in Lithuania, paper argues and concludes, the concept of identity status as elaborated by J.Marcia.